The next millennium and epidemiology: searching for information Próximo milênio e epidemiologia: em busca da informação - Luis David Castiel (Cadernos de Saúde Pública, 1998)
On the eve of the new millennium, it has become 'natural' to admit the emergence of tendencies to perform evaluations and inventories of the past and attempts to forecast future scenarios. While recognizing the ensuing uncertainties, the current paper takes this point of view as the point of departure for proposing a discussion on the future directions and prospects of epidemiology. Based on the pertinent analyses performed by the Sussers (father and son), I approach and discuss the scope and limits of new aspects assumed by the field, especially to the extent that it has included techniques and instruments from bioinformatics and molecular biology. In the latter areas (amongst many others), the notion of information has gained enormous importance. I then proceed to analyze the conceptual origins and shifts in this notion, in addition to possible repercussions and effects on the field of biological sciences in general and their research practices in particular. inclinações para procederem-se a avaliações e balanços do passado e a tentativas de prever-se cenários futuros. Este texto parte deste ponto de vista reconhecendo suas incertezas para propor uma discussão dos rumos e perspectivas da epidemiologia. A partir das análises nesta direção pelos Sussers (pai e filho), são abordadas e discutidas o alcance e os limites de novos aspectos assumidos pela disciplina, especialmente, ao incluir técnicas e instrumentos da bioinformática e da biologia molecular. Nestas áreas (entre muitas outras), é notável o fato da noção de informação possuir enorme importância. São, então, analisadas origens e deslocamentos conceituais desta noção e possíveis repercussões e efeitos no campo das ciências biológicas, em geral, e de suas práticas de pesquisa, em particular.